Corrupting cartels: An overview of the Petrobras case - Klenio Barbosa; Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2019)
This paper provides an overview of the corruption case and the connected cartels that affected one of the biggest Brazilian state-owned companies, Petrobras, and the highly controversial 'Operation Car Wash'. We focus on the behavior of cartel members and study the size of the contracts affected or potentially affected by the illegal activity, comparing them with comparable sets of contracts selected with three different matching approaches.
Keywords: F19; 330; Corruption; Cartels; Brazil